Peran Kesiswaan Madrasah Tsanawiyah swasta (MTS.s) Moti Verbond Ternate - Boko, Yusri A.; Abas, Thalib (Peneliti.net, 2023)
This research has a goal; 1) describe the role of students at the private Moti Verbond Ternate Madrasah Tsanawiyah; 2) describe the student obstacles at Madrasah Tsanawiyah.private Moti Verbond. Research location Moti Verbond private Tsanawiyah Madrasah, Moti District, Ternate City. The research time starts from 1 September-21 October 2023. Data sources can be; informants, places and events/events, documentation. Data collection techniques use interview guidelines, observation and documentation. Data analysis techniques include data reduction, data presentation and drawing conclusions. The results of this research show that, 1) The role of students at the private Moti Verbond Tsanawiyah Madrasah is to develop plans before accepting new students, coordinating with the head of the madrasah, and holding meetings to form the new student admissions committee. Collaborating with parents to prevent children's delinquency, always developing students' talents and interests even though there are many talents that have not been touched, providing support for students to study diligently when they finish school, and always taking inventory of outgoing and incoming letters in the New Student Introduction Orientation activities. 2) Obstacles were found, in the form of children's complaints about post-semester extracurricular activities which were limited to quizzing and reading poetry. Students want more than one or two types of competitions. There is still a lack of discipline among students when they come to school. This becomes difficult because parents' understanding is not yet integrated with student programs. There has been no grouping of students at all through special data collection..